High fat, high sucrose diet promotes increased expression of ACE2 receptor in the SIV-infected host: implications for SARS-CoV-2 infection - Delery, Elizabeth C.; Levitt, Danielle E.; Amedee, Angela M.; Molina, Patricia E.; Simon, Liz (Frontiers in Nutrition, 2024)
Introduction People with pre-existing conditions, including metabolic comorbidities, are at greater risk for complications of SARS-CoV-2 infection and expression of machinery required for viral entry into host cells may be a contributing factor. This study tested the hypothesis that high fat, high sucrose diet (HFSD) and alcohol use increase expression of angiotensin converting enzyme 2 (ACE2) receptor and transmembrane serine protease 2 (TMPRSS2) in tissues isolated from simian immunodeficiency virus (SIV) infected macaques, the most clinically relevant model for the study of HIV. Methods Biospecimens obtained from a longitudinal study of SIV-infected, antiretroviral therapy (ART)-treated female rhesus macaques (Macaca mulatta) were used to determine whether HFSD and chronic binge alcohol (CBA) increased ACE2 and TMPRSS2 protein and gene expression. Macaques (n = 10) were assigned to HFSD or standard diet (SD) for 3 months before CBA or vehicle administration. Three months later, macaques were infected with SIV; ART was initiated 2.5 months thereafter. Tissue samples including lung, pancreas, and kidney were collected at study endpoint (12 months post-SIV infection). Results Protein expression of ACE2 in the lung, whole pancreas, and pancreatic islets was significantly greater in HFSD- than SD-fed macaques with no significant differences in protein expression of TMPRSS2 or mRNA expression of ACE2 or TMPRSS2. CBA did not significantly alter any measures. Discussion The increased ACE2 receptor expression observed in lung and pancreas of SIV-infected HFSD-fed female rhesus macaques aligns with reports that diet may increase susceptibility to COVID-19. These data provide direct evidence for a link between dietary quality and cellular adaptations that may increase the risk for SARS-CoV-2 infection.